Lymph Flow Induces the Postnatal Formation of Mature and Functional Meningeal Lymphatic Vessels - Bálint, László; Ocskay, Zsombor; Deák, Bálint András; Aradi, Petra; Jakus, Zoltán (Frontiers in Immunology, 2020)
Recently, the presence of lymphatic structures has been demonstrated in the dura mater, which in contrast to the classical view indicating the lack of lymphatics in the central nervous system (CNS). Moreover, the role of meningeal lymphatics in the pathogenesis of Alzheimer’s disease and multiple sclerosis was suggested. However, the possible regulators of the developmental program and function of meningeal lymphatics remain unclear. Here, we aimed at characterizing the lymph flow dependence of the developmental program and function of the meningeal lymphatics. First, we demonstrated that lymphatics present in the dura mater are involved in the uptake and transport of macromolecules from the CNS. Meningeal lymphatics develop during the postnatal period which process involves the maturation of the vessels. The formation of mature meningeal lymphatics coincides with the increase of the drainage of macromolecules from the CNS to the deep cervical lymph nodes. Importantly, the structural remodeling and maturation of meningeal lymphatics is impaired in Plcg2-/- mice with reduced lymph flow. Furthermore, macromolecule uptake and transport by the meningeal lymphatics are also affected in Plcg2-/- mice. Collectively, lymph flow-induced mechanical forces are required for the postnatal formation of mature and functional meningeal lymphatic vessels. Defining lymph flow-dependence of the development and function of meningeal lymphatics may lead to better understanding of the pathogenesis of neurological diseases including Alzheimer’s disease and multiple sclerosis.